Exploring Grammatical and Semantic Profiles of Angry and Mad: A Corpus-Based Study - Saskara Tranggana Suari, Ida Ayu; Rajeg, Gede Primahadi Wijaya; Sudipa, I Nengah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This paper investigates how two near-synonymous emotion words (i.e., ANGRY and MAD) would differ in their grammatical (i.e., morphological) and semantic profiles based on data from the Corpus of Contemporary American English (COCA). Morphologically, we analyzed the distribution of verbal inflectional morphologies of these words overall and across different text types/genres in COCA. Semantically, we explored the preferred semantic category of the Experiencer and Stimulus collocates of ANGRY and MAD. In that way, we adopted both quantitative and qualitative methods. We showed that the base verbal form anger is very prominent across genres compared to the base form madden. Similarly, the -ed and third-person singular -s forms are more predominant for ANGER than for MADDEN. In contrast, the -ing form of maddening is far more common than angering. Semantically, angry predominantly collocates with Kinship-based Experiencer than mad. Both adjectives attract distinct types of Experiencer nouns from the social and political relation fields. In terms of the stimulus, mad attracts collocates from the semantic field of emotion and values more predominantly than angry. In sum, corpus analyses help reveal grammatical and semantic differences between near-synonyms such as ANGRY and MAD.